Method for producing carboxylic acid thioester

By using a strong acid medium as a catalyst in the reaction between carbonic acid and thiol, the problems of waste and resource consumption in the production process of carbonic acid thiol in the prior art are solved, and efficient, economical and environmentally friendly production results are achieved.

JP7653307B2Active Publication Date: 2025-03-28ORGANO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021094401
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-04
Publication Date
2025-03-28
Estimated Expiration
2041-06-04

AI Technical Summary

Technical Problem

The prior art has waste problems in the production of thiocarbonate, especially when using carbonate as raw materials, it will produce a large number of by-products, and some processes require the use of rare resources hafnium and the need to stop the reaction for the termination step, resulting in high economic and environmental costs.

Method used

The reaction method of carbonic acid and thiol in a strong acid medium is adopted, and a non-particle organic pore strong acid medium is used as a catalyst to achieve efficient production of carbonyl thioesters by controlling the structure and performance of the catalyst.

Benefits of technology

This method reduces the generation of by-products, improves production efficiency, reduces dependence on rare resources, and simplifies the process flow, achieving an economical and environmentally friendly production method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653307000003
    Figure 0007653307000003
  • Figure 0007653307000004
    Figure 0007653307000004
  • Figure 0007653307000005
    Figure 0007653307000005
Patent Text Reader

Abstract

To provide a method for producing a carboxylic thioester that can be produced by a simple operation, allows reduction in the amount of waste, and has sustainability.SOLUTION: A method for producing a carboxylic thioester includes reacting a carboxylic acid with a thiol in the presence of a solid acid catalyst to produce a carboxylic thioester, the solid acid catalyst being a strong acid cation exchange resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a carboxylic acid thioester. [Background technology]

[0002] Carboxylic acid thioesters are widely used as raw materials for the synthesis of sulfur-containing compounds used in functional materials such as pharmaceuticals, agricultural chemicals, liquid crystals, etc. A method for producing a carboxylic acid thioester is generally known in which a carboxylic acid or a carboxylic acid derivative is reacted with a thiol.

[0003] For example, Patent Document 1 describes a method in which a carboxylic acid anhydride is reacted with a thiol in the presence of an equivalent amount of a carbonate ester and a catalytic amount of an alkali salt or an alkaline earth salt.

[0004] Patent Document 2 and Non-Patent Document 1 describe a method in which a carboxylic acid is reacted with a thiol in the presence of a catalytic amount of trifluorosulfonic acid or Nafion.

[0005] Non-Patent Document 2 describes a method in which a carboxylic acid is reacted with a thiol in the presence of a catalytic amount of hafnium (IV) chloride.

[0006] Non-Patent Document 3 describes a method in which a carboxylic acid is reacted with a thiol in the presence of a catalytic amount of a perfluoropyridinium salt. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 6627653 [Patent Document 2] Patent No. 3777324 [Non-patent literature]

[0008] [Non-Patent Document 1] Chemistry Communication, 2002, pp. 94-95 [Non-Patent Document 2] Tetrahedron, Volume 58, Issue 41, Pages 8179-8188 [Non-Patent Document 3] Green Chemistry, 2006, No. 8, pp. 1022-1027 Summary of the Invention [Problem to be solved by the invention]

[0009] However, in the production method described in Patent Document 1, since a carboxylic anhydride is used as a raw material, an equal amount of a carboxylic acid is by-produced, and an equal amount of a by-product derived from the activator carbonate ester is also produced. Since the by-product needs to be removed in the production process, a large amount of waste is generated, which is problematic from the economic and environmental standpoints.

[0010] The manufacturing method described in Non-Patent Document 2 uses hafnium, which is a rare resource, and although the details are unclear, there is no mention of recovering the hafnium catalyst, which poses problems from the perspective of sustainability.

[0011] The production methods described in Patent Document 2, Non-Patent Document 1, and Non-Patent Document 3 require a step of terminating the reaction with an alkaline aqueous solution or the like, and thus have problems in terms of production operations.

[0012] An object of the present invention is to provide a method for producing a carboxylic acid thioester which is simple in its production operation, can reduce the amount of waste, and is sustainable. [Means for solving the problem]

[0013] The present invention relates to a method for producing a carboxylic acid thioester, comprising reacting a carboxylic acid with a thiol in the presence of a solid acid catalyst to produce a carboxylic acid thioester, the solid acid catalyst being Non-particulate organic porous strongly acidic cation exchanger The present invention relates to a method for producing a carboxylic acid thioester,

[0014] In the method for producing a carboxylic acid thioester, the strongly acidic cation exchange resin preferably has a cation exchange capacity of more than 1 mg equivalent / g.

[0016] In the method for producing a carboxylic acid thioester, the non-particulate organic porous strongly acidic cation exchanger preferably comprises a continuous skeleton phase and a continuous pore phase, the thickness of the continuous skeleton being in the range of 1 to 100 μm, the average diameter of the continuous pores being in the range of 1 to 1000 μm, the total pore volume being in the range of 0.5 to 50 mL / g, the cation exchange capacity per weight in a dry state being in the range of 1 to 5 mg equivalent / g, and the cation exchange groups being distributed throughout the non-particulate organic porous strongly acidic cation exchanger. Effect of the Invention

[0017] According to the present invention, it is possible to provide a method for producing a carboxylic acid thioester which is simple in production operation, can reduce the amount of waste, and is sustainable. [Brief description of the drawings]

[0018] [Figure 1] 1 is a SEM photograph of a first monolith morphology example. [Diagram 2] 1 is a SEM photograph of a second monolith morphology example. [Diagram 3] 11 is an SEM photograph of a third monolith morphology example. [Figure 4] This is a transfer of the skeleton portion shown as a cross section of the SEM photograph in FIG. [Diagram 5] 11 is an SEM photograph of a fourth monolith morphology example. [Figure 6] FIG. 13 is a schematic diagram of the co-continuous structure of the fourth monolith. [Figure 7] 1 is a SEM photograph of an example of the morphology of the monolith intermediate (4). [Figure 8] FIG. 4 is a schematic cross-sectional view of a protrusion. [Figure 9] 5 is a SEM photograph of an example of the monolith shape of No. 5-1. [Figure 10] 2 is a SEM photograph of a monolith intermediate obtained in an example. [Figure 11] 1 is a SEM photograph of a monolith obtained in an example. [Figure 12] 4 is a result of EPMA measurement showing the distribution state of sulfur on the surface of the monolithic cation exchanger obtained in the example. [Figure 13] 4 is a result of EPMA measurement showing the distribution state of sulfur in the cross section of the framework of the monolithic cation exchanger obtained in the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The following describes an embodiment of the present invention. The embodiment is merely an example of implementing the present invention, and the present invention is not limited to the embodiment.

[0020] <Method of producing carboxylic acid thioester> The method for producing a carboxylic acid thioester according to the present embodiment is a method for producing a carboxylic acid thioester by reacting a carboxylic acid with a thiol in the presence of a solid acid catalyst, where the solid acid catalyst is a strongly acidic cation exchange resin.

[0021] As a result of intensive research, the present inventors have found that a carboxylic acid thioester can be obtained by a simple manufacturing procedure by reacting a carboxylic acid and a thiol as raw materials with a strong acid cation exchange resin, which is a common solid material, as a catalyst. This method can reduce the amount of waste. In addition, this method is a sustainable method.

[0022] According to the method for producing a carboxylic acid thioester according to the present embodiment, since carboxylic acid and thiol are used as raw materials, the by-product is water, and the carboxylic acid thioester can be obtained economically and with a smaller environmental impact than conventional methods. In addition, the carboxylic acid thioester can be obtained by removing the strong acid cation exchange resin, which is a solid acid catalyst, after the reaction. Therefore, the carboxylic acid thioester can be obtained by a simple production operation without performing the reaction termination step and purification step required in conventional methods. In addition, since the strong acid cation exchange resin, which is a familiar resource, is used as a catalyst, the carboxylic acid thioester can be obtained by a highly sustainable method.

[0023] [Carboxylic Acid] The carboxylic acid used as the raw material is represented by the following general formula (I). 1 represents an optionally substituted hydrocarbon group having 1 to 30 carbon atoms. R 1 -COOH (I)

[0024] R 1 Examples of the hydrocarbon group having 1 to 30 carbon atoms represented by the formula (1) include saturated aliphatic hydrocarbon groups, unsaturated aliphatic hydrocarbon groups such as alkenyl groups and alkynyl groups, and aromatic hydrocarbon groups. The saturated aliphatic hydrocarbon group and the unsaturated aliphatic hydrocarbon group may be linear, branched, monocyclic, or polycyclic, and the aromatic hydrocarbon group may be condensed.

[0025] R 1 The substituent that may be substituted on the hydrocarbon group having 1 to 30 carbon atoms represented by the formula (I) is not particularly limited as long as it does not inhibit the reaction, and examples thereof include an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, an alkynyl group having 2 to 30 carbon atoms, an alkoxy group having 1 to 30 carbon atoms, a nitro group, a cyano group, an amino group, etc. The alkyl group, alkenyl group, alkynyl group, and alkoxy group may be linear, branched, monocyclic, or polycyclic.

[0026] [Thiol] The thiol used as the raw material is represented by the following general formula (II): 2 R in general formula (I) 1 is synonymous with. R 2 -SH (II)

[0027] [Strongly acidic cation exchange resin] The strongly acidic cation exchange resin used as a catalyst is an ion exchange resin into which a sulfonic acid group, a phosphoric acid group, or the like is introduced as a cation exchange group. The strongly acidic cation exchange resin has a cation exchange capacity of more than 1 mg equivalent / g. The strongly acidic cation exchange resin preferably has a cation exchange capacity of more than 1 mg equivalent / g and not more than 5 mg equivalent / g. If the cation exchange capacity is not more than 1 mg equivalent / g, the resin does not function as a catalyst in the method for producing a carboxylic acid thioester according to the present embodiment. Even if the cation exchange capacity exceeds 5 mg equivalent / g, there are cases in which an improvement in production efficiency cannot be expected.

[0028] The type of strongly acidic cation exchange resin includes a particulate organic porous cation exchanger, a non-particulate organic porous cation exchanger, etc. In the case of a particulate organic porous cation exchanger, there is no particular limitation so long as the cation exchange capacity is greater than 1 mg equivalent / g, and examples thereof include Amberlyst (trademark) 16WET, Amberlyst (trademark) 15DRY, and Amberlite (trademark) XH2071H (all manufactured by Organo Corporation).

[0029] The strongly acidic cation exchange resin may be pretreated as necessary before use, for example by converting it into a free acid (H form) or by drying the strongly acidic cation exchange resin.

[0030] The amount of the strong acid cation exchange resin used is not particularly limited as long as it is an amount that can produce a carboxylic acid thioester, but is, for example, 10 to 1000% by mass based on the raw carboxylic acid. If the amount is less than 10% by mass based on the raw carboxylic acid, the production efficiency may decrease, and even if more than 1000% by mass is used, a significant improvement in the effect may not be expected.

[0031] [Non-particulate organic porous strong acid cation exchanger] A non-particulate organic porous cation exchanger is a monolithic organic porous material having a continuous framework phase and a continuous pore phase, in which a cation exchange group has been introduced. The monolithic organic porous material has a large number of communicating holes that serve as flow paths between the frameworks. In this specification, the term "monolithic organic porous material" is also referred to simply as "monolith", the term "monolithic organic porous cation exchanger" is also referred to simply as "monolith cation exchanger", and the term "monolithic organic porous intermediate", which is an intermediate (precursor) in the production of a monolith, is also referred to simply as "monolith intermediate".

[0032] The structure of this non-particulate organic porous cation exchanger is disclosed in JP-A-2002-306976, JP-A-2009-007550, JP-A-2009-062512, JP-A-2009-067982, and JP-A-2009-108294.

[0033] The non-particulate organic porous cation exchanger preferably comprises a continuous framework phase and a continuous pore phase, the thickness of the continuous framework being in the range of 1 to 100 μm, the average diameter of the continuous pores being in the range of 1 to 1000 μm, the total pore volume being in the range of 0.5 to 50 mL / g, the cation exchange capacity per weight in a dry state being in the range of 1 to 5 mg equivalent / g, and the cation exchange groups being distributed in the organic porous cation exchanger. The continuous framework phase and the continuous pore phase are observed by SEM images.

[0034] The thickness of the continuous skeleton of the non-particulate organic porous cation exchanger in a dry state is preferably in the range of 1 to 100 μm. The thickness of the continuous skeleton of the non-particulate organic porous cation exchanger in a dry state is determined by SEM observation. If the thickness of this continuous skeleton is less than 1 μm or more than 100 μm, the contact between the treated liquid and the monolithic cation exchanger during the reaction becomes insufficient, which may result in a decrease in cation exchange performance and a decrease in reaction efficiency.

[0035] The average diameter of the continuous pores of the non-particulate organic porous cation exchanger in a dry state is preferably in the range of 1 to 1000 μm. The average diameter of the continuous pores of the non-particulate organic porous cation exchanger in a dry state is measured by mercury intrusion porosimetry and refers to the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry. If the average diameter of the continuous pores is less than 1 μm or exceeds 1000 μm, the contact between the treated liquid and the monolithic cation exchanger during the reaction becomes insufficient, which may result in a decrease in cation exchange performance and a decrease in reaction efficiency.

[0036] The total pore volume of the non-particulate organic porous cation exchanger in a dry state is preferably in the range of 0.5 to 50 mL / g. The total pore volume of the non-particulate organic porous cation exchanger in a dry state is measured by mercury intrusion porosimetry. If the total pore volume is less than 0.5 mL / g, the contact between the treated liquid and the monolithic cation exchanger during the reaction may be insufficient. If the total pore volume exceeds 50 mL / g, the mechanical strength of the non-particulate organic porous cation exchanger may decrease, and ease of operation may be impaired.

[0037] The cation exchange capacity per unit weight of the non-particulate organic porous cation exchanger in a dry state is preferably in the range of 1 to 5 mg equivalent / g. The cation exchange capacity per unit weight of the non-particulate organic porous cation exchanger in a dry state is measured by a method such as neutralization titration or precipitation titration. If the cation exchange capacity is less than 1 mg equivalent / g, the amount of cations that can be exchanged and supported is reduced, and the reaction efficiency may decrease. If the cation exchange capacity exceeds 5 mg equivalent / g, the condition of the cation exchange group introduction reaction becomes severe, and the oxidative deterioration of the monolith may progress significantly.

[0038] In the non-particulate organic porous cation exchanger, the introduced cation exchange groups are preferably distributed not only on the surface of the monolith but also inside the skeleton of the monolith, i.e., in the organic porous cation exchanger, and more preferably distributed uniformly. "Cation exchange groups are uniformly distributed in the organic porous cation exchanger" means that the cation exchange groups are distributed on the surface and inside the skeleton of the organic porous cation exchanger at least on the order of μm. The distribution of the cation exchange groups is confirmed by using an electron probe microanalyzer (EPMA). If the cation exchange groups are distributed not only on the surface of the monolith but also inside the skeleton of the monolith, the physical and chemical properties of the surface and inside of the monolith can be made almost uniform, improving the durability against swelling and shrinkage.

[0039] In the non-particulate organic porous cation exchanger, the material constituting the continuous skeleton is an organic polymer material having a crosslinked structure, which preferably contains 0.1 to 30 mol % of crosslinked structural units, more preferably 0.1 to 20 mol %, of the total structural units constituting the organic polymer material.

[0040] The type of organic polymer material is not particularly limited, and examples thereof include aromatic vinyl polymers such as polystyrene, poly(α-methylstyrene), polyvinyltoluene, polyvinylbenzyl chloride, polyvinylbiphenyl, and polyvinylnaphthalene; polyolefins such as polyethylene and polypropylene; poly(halogenated polyolefins) such as polyvinyl chloride and polytetrafluoroethylene; nitrile polymers such as polyacrylonitrile; and crosslinked polymers such as (meth)acrylic polymers such as polymethyl methacrylate, polyglycidyl methacrylate, and polyethyl acrylate. The organic polymer material may be a polymer obtained by copolymerizing a single vinyl monomer and a crosslinking agent, or a polymer obtained by polymerizing multiple vinyl monomers and a crosslinking agent, or may be a blend of two or more polymers. Among these organic polymer materials, crosslinked polymers of aromatic vinyl polymers are preferred because of the ease of forming a continuous structure, the ease of introducing a cation exchange group, high mechanical strength, and high stability against acids or alkalis. In particular, styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers are preferred materials.

[0041] Examples of the cation exchange group introduced into the non-particulate organic porous cation exchanger include a sulfonic acid group and a phosphoric acid group, and the sulfonic acid group is preferred in terms of ease of production.

[0042] [First to fifth monolithic cation exchangers] More specific embodiments of the non-particulate organic porous cation exchanger include, for example, the following first monolithic organic porous cation exchanger (monolithic cation exchanger) to fifth monolithic organic porous cation exchanger (monolithic cation exchanger). In the following description, the description of the same configuration as the above non-particulate organic porous cation exchanger is omitted.

[0043] (First monolith cation exchanger) The first monolith cation exchanger has a continuous macropore structure with interconnected macropores and common openings (mesopores) with an average diameter of 1 to 1000 μm in the walls of the macropores, a total pore volume of 1 to 50 mL / g, a cation exchange capacity per weight in a dry state of 1 to 5 mg equivalent / g, and a cation exchange group distributed in the organic porous cation exchanger.

[0044] The first monolithic cation exchanger is a continuous macropore structure having continuous macropores (fine pores) as shown in Fig. 1. The first monolithic cation exchanger and a method for producing it are disclosed in JP-A-2002-306976.

[0045] The first monolith cation exchanger has macropores that are connected to each other and common openings (mesopores) located in the walls of the macropores. The mesopores have overlapping portions where the macropores overlap each other. The overlapping portions of the mesopores preferably have an average diameter in the dry state of 1 to 1000 μm, more preferably in the range of 10 to 200 μm, and even more preferably in the range of 20 to 200 μm. The average diameter of the openings of the first monolith in the dry state is measured by mercury intrusion porosimetry and refers to the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry.

[0046] Most of such first monolith cation exchangers have an open pore structure in which the voids formed by the macropores and mesopores serve as flow paths. If the average diameter of the overlapping parts of the mesopores in a dry state is less than 1 μm or exceeds 1000 μm, the contact between the liquid to be treated and the monolith cation exchanger during the reaction may be insufficient, resulting in a decrease in cation exchange performance and a decrease in reaction efficiency. The number of overlapping macropores is, for example, 1 to 12 in one macropore, and in most cases, 3 to 10. Since the first monolith cation exchanger has the above-mentioned continuous macropore structure, it is possible to form groups of macropores and groups of common pores almost uniformly, and it is possible to remarkably increase the pore volume and specific surface area compared to particle agglomeration type porous bodies such as those described in JP-A-8-252579.

[0047] The total pore volume per weight of the first monolith cation exchanger in a dry state is preferably in the range of 1 to 50 mL / g, more preferably in the range of 2 to 30 mL / g. If the total pore volume per weight in a dry state is less than 1 mL / g, the contact area per unit cross-sectional area may become small, resulting in a decrease in processing capacity. If the total pore volume per weight in a dry state exceeds 50 mL / g, the mechanical strength may decrease, resulting in a decrease in ease of operation.

[0048] The cation exchange capacity per weight in a dry state is as described above. Furthermore, the fact that "cation exchange groups are distributed in the organic porous cation exchanger" is as described above.

[0049] (First method for producing monolithic cation exchanger) The first monolithic cation exchanger can be produced, for example, by the following method.

[0050] For example, an oil-soluble monomer not containing a cation exchange group, a surfactant, water, and optionally a polymerization initiator can be mixed to obtain a water-in-oil emulsion, which can then be polymerized to form a first monolith.

[0051] The oil-soluble monomer not containing a cation exchange group used in the production of the first monolith refers to a monomer that does not contain a cation exchange group, has low solubility in water, and is lipophilic. Examples of this monomer include styrene, α-methylstyrene, vinylbenzyl chloride, ethylene, propylene, acrylonitrile, and methacrylonitrile. These monomers can be used alone or in combination of two or more. However, it is preferable to select a crosslinkable monomer such as divinylbenzene as at least one component of the oil-soluble monomer and set its content in the range of, for example, 0.3 to 10 mol%, preferably 0.3 to 5 mol%, of the total oil-soluble monomers, in order to quantitatively introduce the cation exchange group in a later step and ensure sufficient mechanical strength for practical use.

[0052] The surfactant used in the production of the first monolith is not particularly limited as long as it can form a water-in-oil (W / O) emulsion when an oil-soluble monomer not containing a cation exchange group is mixed with water. Examples of the surfactant include non-cationic surfactants such as sorbitan monooleate, sorbitan monolaurate, and polyoxyethylene nonylphenyl ether; anionic surfactants such as potassium oleate, sodium dodecylbenzenesulfonate, and dioctyl sodium sulfosuccinate; cationic surfactants such as distearyl dimethyl ammonium chloride; and amphoteric surfactants such as lauryl dimethyl betaine. These surfactants can be used alone or in combination of two or more. A water-in-oil emulsion is an emulsion in which the oil phase is the continuous phase and water droplets are dispersed therein. The amount of surfactant added may be, for example, in the range of about 2 to 70% of the total amount of the oil-soluble monomer and the surfactant. In order to control the shape and size of the cells in the monolith, alcohols such as methanol and stearyl alcohol; carboxylic acids such as stearic acid; hydrocarbons such as octane, dodecane, and toluene; cyclic ethers such as tetrahydrofuran and dioxane, etc. can also be made to coexist in the system.

[0053] In the manufacture of the first monolith, when forming a monolith by polymerization, the polymerization initiator used as necessary is preferably a compound that generates radicals by heat and light irradiation. The polymerization initiator may be water-soluble or oil-soluble, for example, azobisisobutyronitrile, azobisdimethylvaleronitrile, azobiscyclohexanenitrile, azobiscyclohexanecarbonitrile, benzoyl peroxide, potassium persulfate, ammonium persulfate, hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, tetramethylthiuram disulfide, etc. However, in some cases, there are systems in which polymerization proceeds only by heating or light irradiation without adding a polymerization initiator, so in such systems, it is not necessary to add a polymerization initiator.

[0054] In the production of the first monolith, various polymerization conditions for polymerizing the water-in-oil emulsion can be selected depending on the type of monomer, initiator system, etc. When azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, etc. are used as the polymerization initiator, for example, in a sealed container under an inert atmosphere, for example, at 30 to 100°C for 1 to 48 hours, the polymerization can be performed, for example, in a sealed container under an inert atmosphere, at 0 to 30°C for 1 to 48 hours. After the polymerization is completed, the contents are taken out and subjected to Soxhlet extraction with a solvent such as isopropanol to remove unreacted monomers and residual surfactants, to obtain the first monolith.

[0055] Methods for introducing cation exchange groups into the first monolith include, for example, the following methods (1) and (2). (1) Instead of a monomer that does not contain a cation exchange group, a monomer that contains a cation exchange group, for example, the oil-soluble monomer that does not contain a cation exchange group, can be polymerized with a monomer to which a cation exchange group has been introduced, to produce a monolith cation exchanger in one step. (2) A monomer that does not contain a cation exchange group can be polymerized to form the first monolith, and then a cation exchange group can be introduced.

[0056] There are no particular limitations on the method for introducing a cation exchange group into the first monolith, and known methods such as polymer reaction and graft polymerization can be used. For example, a method of reacting a monolith of a styrene-divinylbenzene copolymer with concentrated sulfuric acid, or a method of reacting a monolith of a styrene-divinylbenzene copolymer with chlorosulfonic acid in an organic solvent can be mentioned.

[0057] (Second monolith cation exchanger) The second monolith cation exchanger is a monolith cation exchanger in which organic polymer particles having an average particle size of 1 to 50 μm are aggregated to form a three-dimensionally continuous skeleton, the skeleton having three-dimensionally continuous pores having an average diameter of 20 to 100 μm between the skeletons, a total pore volume in the range of 1 to 10 mL / g, a cation exchange capacity per weight in a dry state in the range of 1 to 5 mg equivalent / g, and cation exchange groups distributed in the organic porous cation exchanger.

[0058] The second monolith cation exchanger is a particle aggregate type structure in which particles are aggregated, as shown in Fig. 2. The second monolith cation exchanger and a method for producing the same are disclosed in JP 2009-007550 A.

[0059] The second monolith cation exchanger has a three-dimensionally continuous skeleton formed by aggregation of organic polymer particles having a crosslinked structural unit and an average particle diameter in a dry state of preferably 1 to 50 μm, more preferably 1 to 30 μm. The second monolith cation exchanger has three-dimensionally continuous pores (continuous pores) between the continuous skeletons, the average diameter in a dry state of preferably 20 to 100 μm, more preferably 20 to 90 μm. An SEM photograph is taken of an arbitrarily extracted part of the cross section of the second monolith cation exchanger in a dry state, the diameters of the organic polymer particles of all the particles in the SEM photograph are measured, and the average value of these is taken as the average particle diameter. The average diameter of the continuous pores in a dry state is determined by mercury intrusion porosimetry, as in the case of the first monolith cation exchanger.

[0060] If the average particle diameter of the organic polymer particles is less than 1 μm in a dry state, the average diameter of the continuous pores between the skeletons may be small, less than 20 μm in a dry state. If the average particle diameter of the organic polymer particles exceeds 50 μm, the contact between the liquid to be treated and the monolith cation exchanger during the reaction may be insufficient, the cation exchange performance may be reduced, and the reaction efficiency may be reduced. In addition, if the average diameter of the above-mentioned continuous pores is less than 20 μm or exceeds 100 μm in a dry state, the contact between the liquid to be treated and the monolith cation exchanger during the reaction may be insufficient, the cation exchange performance may be reduced, and the reaction efficiency may be reduced.

[0061] The total pore volume per weight of the second monolith cation exchanger in a dry state is preferably in the range of 1 to 10 mL / g. If the total pore volume is less than 1 mL / g, the contact amount per unit cross-sectional area becomes small, and the processing capacity may decrease. If the total pore volume exceeds 10 mL / g, the mechanical strength decreases, and the ease of operation may be impaired.

[0062] The cation exchange capacity per weight in a dry state is as described above. Furthermore, the fact that "cation exchange groups are distributed in the organic porous cation exchanger" is as described above.

[0063] (Second method for producing monolithic cation exchanger) The second monolithic cation exchanger can be prepared, for example, by the following method.

[0064] For example, a vinyl monomer, a specific amount of a cross-linking agent, an organic solvent and a polymerization initiator can be mixed and polymerized in a static state to obtain a second monolith.

[0065] The vinyl monomer used in the preparation of the second monolith is similar to the monomer used in the preparation of the first monolith.

[0066] The crosslinking agent used in the production of the second monolith preferably contains at least two polymerizable vinyl groups in the molecule and is highly soluble in an organic solvent. Examples of the crosslinking agent include divinylbenzene, divinylbiphenyl, and ethylene glycol dimethacrylate. These crosslinking agents can be used alone or in combination of two or more. Preferred crosslinking agents are aromatic polyvinyl compounds such as divinylbenzene, divinylnaphthalene, and divinylbiphenyl, from the viewpoints of high mechanical strength and stability against hydrolysis. The amount of the crosslinking agent used relative to the total amount of the vinyl monomer and the crosslinking agent ({crosslinking agent / (vinyl monomer+crosslinking agent)}×100) is, for example, in the range of 1 to 5 mol%, preferably in the range of 1 to 4 mol%.

[0067] The organic solvent used in the production of the second monolith is an organic solvent in which the vinyl monomer and the crosslinking agent dissolve but the polymer produced by polymerization of the vinyl monomer hardly dissolves, in other words, it is a poor solvent for the polymer produced by polymerization of the vinyl monomer. For example, when the vinyl monomer is styrene, this organic solvent is an alcohol such as methanol, butanol, octanol, etc.; a chain ether such as diethyl ether, ethylene glycol dimethyl ether, etc.; a chain saturated hydrocarbon such as hexane, octane, decane, etc.

[0068] The polymerization initiator used in the production of the second monolith is preferably a compound that generates radicals by heat and light irradiation. The polymerization initiator is preferably oil-soluble. Examples of the polymerization initiator include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobisisobutyric acid dimethyl, 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, ammonium persulfate, tetramethylthiuram disulfide, and the like. The amount of polymerization initiator used relative to the total amount of vinyl monomer and crosslinking agent ({polymerization initiator / (vinyl monomer+crosslinking agent)}×100) is, for example, in the range of about 0.01 to 5 mol %.

[0069] In the production of the second monolith, when, for example, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, or the like is used as the polymerization initiator, the polymerization can be carried out, for example, by heating in a sealed container under an inert atmosphere at, for example, 30 to 100°C for 1 to 48 hours. After the polymerization is completed, the contents are taken out, and the second monolith can be obtained by extraction with a solvent such as acetone in order to remove unreacted vinyl monomer and organic solvent.

[0070] In the production of the second monolith, organic polymer particles having an average particle size of 1 to 50 μm can be aggregated by adjusting the polymerization conditions, such as increasing the amount of crosslinking agent, increasing the monomer concentration, and increasing the temperature. By setting the amount of crosslinking agent used relative to the total amount of vinyl monomer and crosslinking agent to a specific amount, three-dimensionally continuous pores having an average diameter of 20 to 100 μm can be formed between the skeletons. By polymerizing under conditions in which the amount of organic solvent used relative to the total amount of organic solvent, monomer, and crosslinking agent used ({organic solvent / (organic solvent+monomer+crosslinking agent)}×100) is, for example, in the range of 30 to 80% by weight, preferably in the range of 40 to 70% by weight, the total pore volume of the monolith can be set to 1 to 5 mL / g.

[0071] The method for introducing cation exchange groups into the second monolith is similar to the method for introducing cation exchange groups into the first monolith.

[0072] (Third monolith cation exchanger) The third monolith cation exchanger is a monolith cation exchanger having a continuous macropore structure in which bubble-like macropores overlap each other and the overlapping portions form openings with an average diameter of 30 to 300 μm, a total pore volume in the range of 0.5 to 10 mL / g, a cation exchange capacity per weight in a dry state in the range of 1 to 5 mg equivalent / g, cation exchange groups distributed in the organic porous cation exchanger, and in an SEM image of a cut surface of the continuous macropore structure, the area of ​​the framework appearing on the cross section is in the range of 25 to 50% of the image area.

[0073] The third monolith cation exchanger has a continuous macropore structure similar to the first monolith cation exchanger, as shown in Figure 3. The third monolith cation exchanger and a method for producing the same are disclosed in JP 2009-062512 A.

[0074] The continuous pores have overlapping portions where macropores overlap each other. The overlapping portions preferably have an average diameter in the dry state of 30 to 300 μm, more preferably 30 to 200 μm, and even more preferably 40 to 100 μm. This average diameter is measured by mercury intrusion porosimetry and refers to the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry. If the average diameter of the openings in the dry state is less than 30 μm or exceeds 300 μm, contact between the treated liquid and the monolith cation exchanger during the reaction becomes insufficient, resulting in a decrease in cation exchange performance and a decrease in reaction efficiency.

[0075] In the third monolith cation exchanger, in an SEM image of a cut surface of the continuous macropore structure in a dry state, the area of ​​the skeleton portion appearing on the cross section is, for example, in the range of 25 to 50% of the image area, and preferably in the range of 25 to 45%. If the area of ​​the skeleton portion appearing on the cross section is less than 25% of the image area, the skeleton becomes thin, and the mechanical strength decreases, which may impair ease of operation. If the area of ​​the skeleton portion appearing on the cross section is more than 50% of the image area, the skeleton becomes too thick, which may result in insufficient contact between the treated liquid and the monolith cation exchanger during the reaction, and thus may result in reduced reaction efficiency.

[0076] The conditions for obtaining an SEM image may be such that the skeleton part appearing on the cross section of the cut surface is clearly visible, for example, a magnification of 100 to 600 and a photographic area of ​​about 150 mm x 100 mm. SEM observation is preferably performed using three or more images of different cut locations or photographed locations taken at any location on any cut surface of the third monolith cation exchanger, eliminating subjectivity. The third monolith cation exchanger to be cut is in a dry state. The skeleton part of the cut surface in the SEM image will be described with reference to Figs. 3 and 4. In Figs. 3 and 4, the part that is roughly irregular and appears on the cross section is the "skeleton part appearing on the cross section (reference number 12)", the circular pores appearing in Fig. 3 are openings (mesopores), and those with a relatively large curvature or curved surface are macropores (reference number 13 in Fig. 4). The area of ​​the skeleton part appearing on the cross section in Fig. 4 is 28% of the rectangular image area 11.

[0077] In an SEM image, the area of ​​the skeleton appearing in the cross section of the cut surface can be measured by specifying the skeleton through known computer processing, etc., and then calculating it automatically using a computer, etc., or manually. As a manual calculation, there can be mentioned a method of replacing an indefinite shape object with an aggregate of a square, triangle, circle, trapezoid, etc., and stacking them to determine the area.

[0078] The total pore volume per weight of the third monolith cation exchanger in a dry state is preferably in the range of 0.5 to 10 mL / g, more preferably in the range of 0.8 to 8 mL / g. If the total pore volume is less than 0.5 mL / g, the amount of permeating fluid per unit cross-sectional area becomes small, and the processing capacity may decrease. If the total pore volume exceeds 10 mL / g, the mechanical strength may decrease, and the ease of operation may be impaired. Furthermore, the contact efficiency between the liquid to be treated and the monolith cation exchanger during the reaction may decrease.

[0079] The cation exchange capacity per weight in a dry state is as described above. Furthermore, the fact that "cation exchange groups are distributed in the organic porous cation exchanger" is as described above.

[0080] (Third method for producing monolithic cation exchanger) The third monolithic cation exchanger can be produced, for example, by the following method.

[0081] For example, a water-in-oil emulsion is prepared by stirring a mixture of an oil-soluble monomer not containing a cation exchange group, a surfactant, and water. Then, the following steps I, II, and III are carried out to obtain a third monolith. In step I, the water-in-oil emulsion is polymerized to obtain a monolithic organic porous intermediate (hereinafter also referred to as monolith intermediate (3)) having a continuous macropore structure with a total pore volume in the range of 5 to 16 mL / g. In step II, a mixture containing a vinyl monomer, a crosslinking agent having at least two or more vinyl groups in one molecule, an organic solvent in which the vinyl monomer and the crosslinking agent are dissolved but the polymer produced by polymerization of the vinyl monomer is not dissolved, and a polymerization initiator is prepared. In step III, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (3) obtained in step I to obtain a third monolith having a skeleton thicker than that of the monolith intermediate (3).

[0082] Step I is the same as in the first method for producing the monolithic cation exchanger.

[0083] The monolith intermediate (3) obtained in step I has a continuous macropore structure. When this is present in a polymerization system, a porous structure having a sturdy skeleton can be formed using the structure of the monolith intermediate (3) as a model. The crosslink density of the polymer material is preferably in the range of, for example, 0.3 to 10 mol %, and more preferably 0.3 to 5 mol %, of crosslinked structural units relative to the total structural units constituting the polymer material of the monolith intermediate (3).

[0084] The total pore volume per weight in a dry state of the monolith intermediate (3) obtained in step I is, for example, in the range of 5 to 16 mL / g, and preferably in the range of 6 to 16 mL / g. In order to set the total pore volume of the monolith intermediate (3) in the above numerical range, the ratio of monomer to water may be, for example, in the range of about 1:5 to 1:20.

[0085] The monolith intermediate (3) obtained in step I has an average diameter of openings (mesopores) which are overlapping portions of macropores, in the range of, for example, 20 to 200 μm in a dry state.

[0086] Step II is a step of preparing a mixture containing a vinyl monomer, a crosslinking agent having at least two vinyl groups in one molecule, an organic solvent that dissolves the vinyl monomer and the crosslinking agent but not the polymer produced by polymerization of the vinyl monomer, and a polymerization initiator. Note that the order of steps I and II may be any.

[0087] The vinyl monomer used in step II may be any lipophilic vinyl monomer that contains a polymerizable vinyl group in the molecule and has high solubility in an organic solvent, and it is preferable to select a vinyl monomer that produces the same or similar polymer material as the monolith intermediate (3) that is coexisted in the polymerization system. Specific examples of these vinyl monomers are the same as those used in the production of the first monolith.

[0088] The amount of the vinyl monomer used in step II is, for example, in the range of 3 to 50 times, and preferably in the range of 4 to 40 times, by weight, the amount of the monolith intermediate (3) that is allowed to coexist during polymerization.

[0089] The cross-linking agent used in step II is the same as the cross-linking agent used in the preparation of the second monolith.

[0090] The organic solvent used in step II is the same as that used in the production of the second monolith. The amount of the organic solvent used is preferably such that the concentration of the vinyl monomer is, for example, 30 to 80% by weight.

[0091] The polymerization initiator used in step II is the same as the polymerization initiator used in the production of the second monolith.

[0092] In step III, for example, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (3) obtained in step I, to obtain a third monolith having a skeleton thicker than that of the monolith intermediate (3). When the monolith intermediate (3) having a continuous macropore structure is present in the above polymerization system, a third monolith can be obtained.

[0093] In step III, for example, in a reaction vessel, the monolith intermediate (3) is placed in a state of being impregnated with the mixture (solution). The mixture obtained in step II and the monolith intermediate (3) may be mixed in a ratio, for example, such that the amount of vinyl monomer added is in the range of 3 to 50 times, preferably 4 to 40 times, by weight, relative to the monolith intermediate (3). In the reaction vessel, the vinyl monomer and crosslinking agent in the mixture are adsorbed and distributed to the skeleton of the stationary monolith intermediate, and polymerization proceeds within the skeleton of the monolith intermediate (3).

[0094] In the III step, various polymerization conditions are selected depending on the type of monomer, the type of polymerization initiator, and the like. For example, when 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, or the like is used as the polymerization initiator, the polymerization may be carried out, for example, at 30 to 100°C for 1 to 48 hours in a sealed container under an inert atmosphere. By the thermal polymerization, the vinyl monomer and crosslinking agent adsorbed and distributed in the skeleton of the monolith intermediate (3) are polymerized in the skeleton, and the skeleton can be thickened. After the polymerization is completed, the contents are taken out, and for the purpose of removing the unreacted vinyl monomer and the organic solvent, the third monolith can be obtained by extraction with a solvent such as acetone.

[0095] The third monolith cation exchanger can be obtained, for example, by carrying out step IV in which a cation exchange group is introduced into the third monolith obtained in step III. The method for introducing a cation exchange group into the third monolith is the same as the method for introducing a cation exchange group into the first monolith.

[0096] (Fourth monolith cation exchanger) The fourth monolith cation exchanger is a bicontinuous structure consisting of a three-dimensionally continuous skeleton having a thickness of 1 to 60 μm and composed of an aromatic vinyl polymer containing crosslinked structural units in the range of 0.1 to 5.0 mol % of all structural units having cation exchange groups introduced therein, and three-dimensionally continuous pores having an average diameter of 10 to 200 μm between the skeletons, the total pore volume being in the range of 0.5 to 10 mL / g and the cation exchange capacity per weight in a dry state being in the range of 1 to 5 mg equivalent / g, and the cation exchange groups being distributed in the organic porous cation exchanger.

[0097] As shown in Figs. 5 and 6, the fourth monolith cation exchanger has a continuous skeleton phase 1 (continuous skeleton) and a continuous pore phase 2 (continuous pores), which are intertwined to form a bicontinuous structure 10 that is three-dimensionally continuous. The pore phase 2 has high continuity and almost no deviation in size compared to the first and second monoliths. The fourth monolith cation exchanger is considered to have high mechanical strength because of its thick skeleton. The fourth monolith cation exchanger and a method for producing it are disclosed in JP 2009-067982 A.

[0098] The continuous skeleton is composed of a vinyl polymer (such as an aromatic vinyl polymer) containing 0.1 to 5.0 mol % of crosslinked structural units in all structural units to which a cation exchange group has been introduced, and the thickness of the continuous skeleton is three-dimensionally continuous, for example, in the range of 1 to 60 μm, preferably in the range of 3 to 58 μm, in a dry state. If the crosslinked structural units are less than 0.1 mol %, the mechanical strength may be insufficient, and if they exceed 5.0 mol %, the structure of the porous body may easily deviate from the co-continuous structure. If the thickness of this continuous skeleton is less than 1 μm or more than 60 μm in a dry state, the contact between the treated liquid and the monolithic cation exchanger during the reaction may be insufficient, resulting in a decrease in cation exchange performance and a decrease in reaction efficiency.

[0099] The interconnected pores are three-dimensionally connected between the interconnected skeletons with an average diameter of, for example, 10 to 200 μm, preferably 15 to 180 μm, in a dry state. If the average diameter of the interconnected pores is less than 10 μm or exceeds 200 μm in a dry state, the contact between the treated liquid and the monolithic cation exchanger during the reaction becomes insufficient, resulting in a decrease in cation exchange performance and a decrease in reaction efficiency.

[0100] The aforementioned average diameter is measured by mercury intrusion porosimetry and refers to the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry. The thickness of the continuous skeleton in a dry state is determined by SEM observation of the fourth monolith cation exchanger in a dry state. Specifically, SEM observation of the fourth monolith cation exchanger in a dry state is performed at least three times, the thickness of the skeleton in the obtained image is measured, and the average value of these is taken as the thickness of the continuous skeleton. Note that the skeleton is rod-shaped and has a circular cross-sectional shape, but may also include one with a cross-section of different diameters such as an elliptical cross-sectional shape. In this case, the thickness is the average of the minor axis and the major axis.

[0101] The total pore volume per weight of the fourth monolith cation exchanger in a dry state is, for example, in the range of 0.5 to 10 mL / g. If the total pore volume is less than 0.5 mL / g, the amount of permeating fluid per unit cross-sectional area becomes small, and the processing capacity may decrease. If the total pore volume exceeds 10 mL / g, the mechanical strength may decrease, and the ease of operation may be impaired. Furthermore, the contact efficiency between the liquid to be treated and the monolith cation exchanger during the reaction may decrease.

[0102] Examples of vinyl polymers (aromatic vinyl polymers) constituting the continuous backbone include polystyrene, poly(α-methylstyrene), polyvinylbenzyl chloride, etc. The above polymer may be a polymer obtained by copolymerizing a single vinyl monomer and a crosslinking agent, a polymer obtained by polymerizing a plurality of vinyl monomers and a crosslinking agent, or a blend of two or more polymers. Among these organic polymer materials, styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers are preferred because of the ease of forming a co-continuous structure, the ease of introducing a cation exchange group, high mechanical strength, and high stability against acids or alkalis.

[0103] The cation exchange capacity per weight in a dry state is as described above. Furthermore, the fact that "cation exchange groups are distributed in the organic porous cation exchanger" is as described above.

[0104] (Fourth method for producing monolithic cation exchanger) The fourth monolithic cation exchanger can be produced, for example, by the following method.

[0105] For example, the fourth monolith can be obtained by preparing a water-in-oil emulsion and then carrying out the following steps I to III. In step I, for example, the water-in-oil emulsion can be polymerized to obtain a monolithic organic porous intermediate (hereinafter, monolith intermediate (4)) having a continuous macropore structure with a total pore volume of, for example, more than 16 mL / g and 30 mL / g or less. In step II, for example, a mixture containing an aromatic vinyl monomer, a crosslinking agent in the range of, for example, 0.3 to 5 mol % in a total oil-soluble monomer having at least two or more vinyl groups in one molecule, an organic solvent in which the aromatic vinyl monomer and the crosslinking agent are dissolved but the polymer produced by polymerization of the aromatic vinyl monomer is not dissolved, and a polymerization initiator is prepared. In step III, for example, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (4) obtained in step I to obtain a fourth monolith.

[0106] Step I in the fourth method for producing a monolith is the same as in the first method for producing a monolith cation exchanger.

[0107] The monolith intermediate (4) obtained in step I is, for example, an organic polymer material having a crosslinked structure, preferably an aromatic vinyl polymer. The crosslink density of this polymer material is, for example, in the range of 0.1 to 5 mol %, preferably 0.3 to 3 mol %, of crosslinked structural units relative to the total structural units constituting the polymer material.

[0108] The type of polymer material of the monolith intermediate (4) is the same as the type of polymer material of the monolith intermediate (3) in the third method for producing a monolith.

[0109] The total pore volume per weight of the monolith intermediate (4) obtained in step I in a dry state is, for example, more than 16 mL / g and 30 mL / g or less, preferably more than 16 mL / g and 25 mL / g or less. As shown in Fig. 7, the monolith intermediate (4) has a skeleton that is nearly rod-shaped. When this is allowed to coexist in a polymerization system, a porous body with a cocontinuous structure can be formed using the structure of the monolith intermediate (4) as a mold.

[0110] The monolith intermediate (4) obtained in step I has an average diameter of openings (mesopores) which are overlapping portions of macropores, in the range of, for example, 5 to 100 μm in a dry state.

[0111] Step II in the fourth monolith manufacturing method is a step of preparing a mixture containing, for example, an aromatic vinyl monomer, a crosslinking agent in the range of, for example, 0.3 to 5 mol % of all oil-soluble monomers having at least two or more vinyl groups in one molecule, an organic solvent that dissolves the aromatic vinyl monomer and the crosslinking agent but does not dissolve the polymer produced by polymerization of the aromatic vinyl monomer, and a polymerization initiator. Note that the order of steps I and II may be any.

[0112] The aromatic vinyl monomer used in the II step is not particularly limited as long as it is an aromatic vinyl monomer that contains a polymerizable vinyl group in the molecule and is lipophilic and highly soluble in an organic solvent, but it is preferable to select a vinyl monomer that produces the same or similar polymer material as the monolith intermediate (4) that is coexisted in the polymerization system. Specific examples of these vinyl monomers include styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, vinylbiphenyl, vinylnaphthalene, etc. These monomers can be used alone or in combination of two or more. The aromatic vinyl monomers that are preferably used are styrene, vinylbenzyl chloride, etc.

[0113] The amount of the aromatic vinyl monomer used in step II is, for example, in the range of 5 to 50 times, and preferably in the range of 5 to 40 times, by weight, the amount of the monolith intermediate (4) that is allowed to coexist during polymerization.

[0114] The crosslinking agent used in the II step preferably contains at least two polymerizable vinyl groups in the molecule and is highly soluble in an organic solvent. Examples of the crosslinking agent include divinylbenzene, divinylnaphthalene, divinylbiphenyl, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, butanediol diacrylate, etc. These crosslinking agents can be used alone or in combination of two or more. The amount of the crosslinking agent used is, for example, in the range of 0.3 to 5 mol% relative to the total amount of the vinyl monomer and the crosslinking agent (total oil-soluble monomers), and is particularly in the range of 0.3 to 3 mol%. It is preferable to use the crosslinking agent in an amount that is approximately equal to the crosslink density of the monolith intermediate (4) that is coexistent during the vinyl monomer / crosslinking agent polymerization. If the amounts of the two are too far apart, the crosslink density distribution in the produced monolith will be biased, and when a cation exchange group is introduced, cracks may easily occur during the cation exchange group introduction reaction.

[0115] The organic solvent used in the II step is, for example, an organic solvent in which the aromatic vinyl monomer and the crosslinking agent dissolve but the polymer produced by polymerization of the aromatic vinyl monomer does not dissolve, in other words, it is a poor solvent for the polymer produced by polymerization of the aromatic vinyl monomer. For example, when the aromatic vinyl monomer is styrene, the organic solvent is alcohols such as methanol, butanol, octanol, etc.; chain (poly)ethers such as diethyl ether, polyethylene glycol, polypropylene glycol, etc.; chain saturated hydrocarbons such as hexane, heptane, octane, etc.; esters such as ethyl acetate, isopropyl acetate, ethyl propionate, etc. In addition, even if it is a good solvent for polystyrene such as dioxane, THF, or toluene, it can be used as an organic solvent when it is used together with the poor solvent and the amount used is small. The amount of these organic solvents used can be such that the concentration of the aromatic vinyl monomer is, for example, 30 to 80% by weight. If the amount of the organic solvent used deviates from the above range and the aromatic vinyl monomer concentration is less than 30% by weight, the polymerization rate may decrease or the monolith structure after polymerization may deviate from the range of the fourth monolith. On the other hand, if the aromatic vinyl monomer concentration exceeds 80% by weight, the polymerization may proceed too far.

[0116] The polymerization initiator used in step II in the fourth method for producing a monolith is the same as the polymerization initiator used in step II in the third method for producing a monolith.

[0117] Step III in the fourth monolith manufacturing method is, for example, a step in which the mixture obtained in step II is allowed to stand and polymerized in the presence of the monolith intermediate (4) obtained in step I, thereby converting the continuous macropore structure of the monolith intermediate (4) into a co-continuous structure, thereby obtaining a fourth monolith which is a co-continuous structure monolith.

[0118] In step III, for example, in a reaction vessel, the monolith intermediate (4) is placed in a state of being impregnated with the mixture (solution). As described above, the mixture obtained in step II and the monolith intermediate (4) may be mixed in such a ratio that the amount of the aromatic vinyl monomer added is, for example, in the range of 5 to 50 times, preferably in the range of 5 to 40 times, by weight, relative to the monolith intermediate (4). This makes it possible to obtain a fourth monolith having a bicontinuous structure in which pores of appropriate size are three-dimensionally continuous and a thick skeleton is three-dimensionally continuous. In the reaction vessel, the aromatic vinyl monomer and the crosslinking agent in the mixture are adsorbed and distributed to the skeleton of the stationary monolith intermediate (4), and polymerization proceeds within the skeleton of the monolith intermediate (4).

[0119] The polymerization conditions in step III in the fourth monolith manufacturing method are the same as those in step III in the third monolith manufacturing method. The fourth monolith cation exchanger can be obtained by carrying out step IV to introduce a cation exchange group into the fourth monolith obtained in step III. The method for introducing a cation exchange group into the fourth monolith is the same as the method for introducing a cation exchange group into the first monolith.

[0120] (Fifth monolithic cation exchanger) The fifth monolith cation exchanger is a monolith cation exchanger which comprises a continuous skeleton phase and a continuous pore phase, the skeleton having a plurality of particulate bodies with diameters in the range of 4 to 40 μm adhered to the surface or a plurality of protrusions with sizes in the range of 4 to 40 μm formed on the skeleton surface of the organic porous body, the average diameter of the continuous pores being in the range of 10 to 200 μm, the total pore volume being in the range of 0.5 to 10 mL / g, the cation exchange capacity per weight in a dry state being in the range of 1 to 5 mg equivalent / g, and the cation exchange groups being distributed in the organic porous cation exchanger.

[0121] The fifth monolith cation exchanger is a composite structure having an organic porous material with a continuous skeleton phase and a continuous pore phase, and further having a plurality of particles or a plurality of protrusions, and is a composite structure having a large number of particles or a large number of protrusions. The fifth monolith cation exchanger and a method for producing the same are disclosed in JP 2009-108294 A.

[0122] The plurality of particulate bodies are fixed to the skeletal surface of the organic porous body, and have a diameter in the range of, for example, 4 to 40 μm. The plurality of protrusions are formed on the skeletal surface of the organic porous body, and have a size in the range of, for example, 4 to 40 μm in a dry state. The diameter of the particulate bodies or the size of the protrusions is preferably in the range of 4 to 30 μm, and more preferably in the range of 4 to 20 μm. In this specification, the "particulate bodies" and "protrusions" are collectively referred to as "particulate bodies, etc."

[0123] The average diameter of the interconnected pores in a dry state is preferably in the range of 10 to 200 μm.

[0124] The continuous skeletal phase and the continuous pore phase of the fifth monolithic cation exchanger are observed by SEM images. The basic structure of the fifth monolithic cation exchanger includes a continuous macropore structure and a bicontinuous structure. The skeletal phase of the fifth monolithic cation exchanger appears as a continuous columnar structure, a continuous concave wall structure, or a composite of these, and has a shape that is clearly different from a particulate or protruding shape.

[0125] The fifth monolith cation exchanger includes a 5-1 monolith cation exchanger and a 5-2 monolith cation exchanger. The 5-1 monolith cation exchanger is a continuous macropore structure in which bubble-like macropores overlap each other, and the overlapping portions become openings with an average diameter of, for example, 10 to 120 μm in a dry state. The 5-2 monolith cation exchanger is a bicontinuous structure consisting of a three-dimensionally continuous skeleton with a continuous skeleton thickness of, for example, 0.8 to 40 μm in a dry state, and three-dimensionally continuous pores with an average diameter of, for example, 8 to 80 μm in a dry state between the skeletons. The monoliths of the 5-1 and 5-2 monolith cation exchangers before the introduction of the cation exchange groups are called the 5-1 and 5-2 monoliths. The aforementioned average diameter and the thickness of the continuous skeleton in a dry state are determined by the same measurement method as the fourth monolith cation exchanger.

[0126] As shown in (A) to (E) in FIG. 8, the protrusions protruding from the skeleton surface 21 are the protrusions 22a to 22e. As shown in (A), the protrusions 22a have a shape close to a granule. As shown in (B), the protrusions 22b are hemispherical. As shown in (C), the protrusions 22c have a shape like a bulge on the skeleton surface. As shown in (D), the length of the protrusions 22d in the planar direction of the skeleton surface 21 is longer than the length of the protrusions 22d in the direction perpendicular to the skeleton surface 21. As shown in (E), the protrusions 22e have a shape protruding in multiple directions. The size of the protrusions is the length of the part where the width of each protrusion is the largest in the SEM image. As shown in FIG. 9, in the fifth monolith cation exchanger, multiple protrusions are formed on the skeleton surface of the organic porous body.

[0127] In the fifth monolith cation exchanger, the proportion of particles in the range of 4 to 40 μm in the total particles in a dry state is, for example, 70% or more, preferably 80% or more. The proportion of the particles refers to the number ratio of particles of a specific size in the total number of particles in a dry state. The surface of the skeleton phase is covered by all particles for example, 40% or more, preferably 50% or more. The coverage ratio of the surface of the skeleton layer by all particles refers to the area ratio on the SEM image when the surface is observed by SEM, that is, the area ratio when the surface is viewed in plan. If the size of the particles covering the wall surface or skeleton deviates from the above range, the effect of improving the contact efficiency between the fluid and the skeleton surface and inside of the skeleton of the monolith cation exchanger may be easily reduced.

[0128] The fifth monolith cation exchanger in a dry state is observed at least three times under SEM, and the diameter or size of all particles in the SEM image in the whole field of view is calculated to confirm whether particles having a diameter or size in the range of, for example, 4 to 40 μm are observed. If they are observed in the whole field of view, it is determined that particles having a diameter or size in the range of, for example, 4 to 40 μm in a dry state are formed on the skeleton surface of the fifth monolith cation exchanger. In addition, the diameter or size of all particles in the SEM image in the dry state is calculated for each field of view according to the above, and the proportion of particles having a dry state of, for example, 4 to 40 μm in each field of view is determined. If the proportion of particles having a dry state of, for example, 4 to 40 μm in the whole field of view is 70% or more, it is determined that the proportion of particles having a dry state of, for example, 4 to 40 μm in the whole field of view is 70% or more. In addition, the coverage rate of the surface of the skeletal layer by all particles, etc. in the SEM image is determined for each field of view in accordance with the above, and if the coverage rate of the surface of the skeletal layer by all particles, etc. in the entire field of view is 40% or more, it is determined that the coverage rate of the surface of the skeletal layer of the fifth monolith cation exchanger by all particles, etc. is 40% or more.

[0129] In the fifth monolith cation exchanger, if the coverage of the skeletal phase surface by the particulate matter is less than 40%, the effect of improving the contact efficiency between the treated liquid and the inside and surface of the skeletal structure of the monolith cation exchanger may be easily reduced. As a method for measuring the coverage by the particulate matter, an image analysis method using an SEM image of the fifth monolith cation exchanger may be used.

[0130] The total pore volume per weight of the fifth monolith cation exchanger in a dry state is, for example, in the range of 0.5 to 10 mL / g, preferably in the range of 0.8 to 8 mL / g. If the total pore volume is less than 0.5 mL / g, the amount of permeating fluid per unit cross-sectional area becomes small, and the processing capacity may decrease. If the total pore volume exceeds 10 mL / g, the mechanical strength may decrease, and the ease of operation may be impaired. Furthermore, the contact efficiency between the liquid to be treated and the monolith cation exchanger during the reaction may decrease.

[0131] In the fifth monolith cation exchanger, the crosslink density of the polymer material constituting the skeleton may be, for example, in the range of 0.3 to 10 mol %, preferably in the range of 0.3 to 5 mol %, of crosslinked structural units based on the total structural units constituting the polymer material. The organic polymer material constituting the skeleton of the fifth monolith cation exchanger is the same as that of the first monolith cation exchanger.

[0132] In the fifth monolithic cation exchanger, the material constituting the skeletal phase of the organic porous material and the particulate matter formed on the surface of the skeletal phase may be made of the same material having a continuous structure of the same kind, or made of different materials having a continuous structure of different kinds, etc. Examples of materials having a continuous structure of different kinds of different kinds include materials having different types of vinyl monomers, and materials having the same types of vinyl monomers and crosslinking agents but different mixing ratios.

[0133] The fifth monolithic cation exchanger has a thickness of, for example, 1 mm or more, and is distinguished from a membrane-like porous body. The thickness of the fifth monolithic cation exchanger is preferably in the range of 3 to 1000 mm.

[0134] The cation exchange capacity per weight in a dry state is as described above. Furthermore, the fact that "cation exchange groups are distributed in the organic porous cation exchanger" is as described above.

[0135] (Fifth method for producing monolithic cation exchanger) The fifth monolithic cation exchanger can be produced, for example, by the following method.

[0136] The fifth monolith can be obtained, for example, by preparing a water-in-oil emulsion and then carrying out the following steps I to III. In step I, for example, the water-in-oil emulsion can be polymerized to obtain a monolithic organic porous intermediate (hereinafter, monolith intermediate (5)) having a continuous macropore structure with a total pore volume in the range of, for example, 5 to 30 mL / g. In step II, for example, a mixture containing a vinyl monomer, a crosslinking agent having at least two or more vinyl groups in one molecule, an organic solvent that dissolves the vinyl monomer and the crosslinking agent but does not dissolve the polymer produced by polymerization of the vinyl monomer, and a polymerization initiator is prepared. In step III, for example, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (5) obtained in step I to obtain a fifth monolith.

[0137] Step I in the fifth method for producing a monolith is similar to step I in the third method for producing a monolith.

[0138] In the I step, when forming the water-in-oil emulsion, a polymerization initiator may be used as necessary. The polymerization initiator is preferably a compound that generates radicals by heat or light irradiation. The polymerization initiator may be water-soluble or oil-soluble, and examples thereof include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobisisobutyric acid dimethyl, 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, ammonium persulfate, hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, and the like.

[0139] The monolith intermediate (5) obtained in step I has a continuous macropore structure. When this is allowed to coexist in a polymerization system, particulate matter and the like is formed on the surface of the skeletal phase of the continuous macropore structure using the structure of the monolith intermediate (5) as a template, or particulate matter and the like is formed on the surface of the skeletal phase of the cocontinuous structure. The monolith intermediate (5) is an organic polymer material having a crosslinked structure. The crosslink density of the polymer material is, for example, in the range of 0.3 to 10 mol %, preferably 0.3 to 5 mol %, of crosslinked structural units relative to the total structural units constituting the polymer material.

[0140] The type of polymer material of the monolith intermediate (5) is the same as the type of polymer material of the monolith intermediate (3) in the third method for producing a monolith.

[0141] The total pore volume per weight of the monolith intermediate (5) in a dry state obtained in step I is, for example, in the range of 5 to 30 mL / g, and preferably in the range of 6 to 28 mL / g. In order to set the total pore volume of the monolith intermediate (5) in the above numerical range, the ratio (by weight) of monomer to water may be, for example, about 1:5 to 1:35.

[0142] In step I, if the ratio of monomer to water is about 1:5 to 1:20, the monolith intermediate (5) will have a continuous macropore structure with a total pore volume of, for example, 5 to 16 mL / g, and the monolith obtained through step III will be a monolith No. 5-1. On the other hand, if the ratio of monomer to water is about 1:20 to 1:35, the monolith intermediate (5) will have a continuous macropore structure with a total pore volume of, for example, more than 16 mL / g and 30 mL / g or less, and the monolith obtained through step III will be a monolith No. 5-2.

[0143] The monolith intermediate (5) obtained in step I in the fifth monolith production method has openings (mesopores) which are overlapping portions of macropores, with an average diameter in a dry state of, for example, 20 to 200 μm.

[0144] Step II in the fifth monolith production method is the same as step II in the third monolith production method. In step III in the fifth monolith production method, for example, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (5) obtained in step I to obtain the fifth monolith.

[0145] Here, as disclosed in JP-A-7-501140, etc., a particle-aggregation type monolithic organic porous material can be obtained by statically polymerizing a vinyl monomer and a crosslinking agent in a specific organic solvent in the absence of the monolith intermediate (5). On the other hand, when the monolith intermediate (5) having a continuous macropore structure is present in the above polymerization system, the structure of the composite monolith after polymerization changes dramatically, and a fifth monolith having the above-mentioned specific skeletal structure can be obtained, instead of a particle-aggregation structure.

[0146] In the III step in the method for producing the fifth monolith, the internal volume of the reaction vessel is not particularly limited as long as it is large enough to allow the monolith intermediate (5) to exist in the reaction vessel. When the monolith intermediate (5) is placed in the reaction vessel, either one in which a gap is formed around the monolith in a plan view or one in which the monolith intermediate (5) fits almost without any gaps in the reaction vessel may be used. Among these, one in which the fifth monolith after polymerization is hardly subjected to pressure from the inner wall of the vessel and fits almost without any gaps in the reaction vessel is efficient with almost no distortion of the fifth monolith and almost no waste of reaction raw materials, etc. Even if the internal volume of the reaction vessel is large and there is a gap around the fifth monolith after polymerization, the vinyl monomer and crosslinking agent are adsorbed and distributed to the monolith intermediate (5), so that particle aggregate structures are hardly generated in the gaps in the reaction vessel.

[0147] In this step III, for example, the monolith intermediate (5) is placed in a reaction vessel in a state of being impregnated with the mixture (solution). As described above, the mixture obtained in step II and the monolith intermediate (5) may be mixed in such a ratio that the amount of vinyl monomer added is, for example, in the range of 3 to 50 times, preferably in the range of 4 to 40 times, by weight, relative to the monolith intermediate (5). This makes it possible to obtain a fifth monolith, which is a composite monolith having a specific skeleton while having an appropriate opening diameter. In the reaction vessel, the vinyl monomer and crosslinking agent in the mixture are adsorbed and distributed to the skeleton of the stationary monolith intermediate (5), and polymerization proceeds within the skeleton of the monolith intermediate (5).

[0148] In step III in the fifth method for producing a monolith, the polymerization conditions are almost the same as those in step III in the third method for producing a monolith.

[0149] When producing the above-mentioned fifth monolith, if step II or III is carried out under conditions that satisfy at least one of the following conditions (1) to (5), a monolith having particles and the like formed on the skeleton surface can be produced. (1) The polymerization temperature in step III is at least 5° C. lower than the 10-hour half-life temperature of the polymerization initiator. (2) The mole percentage of the crosslinking agent used in step II is at least twice the mole percentage of the crosslinking agent used in step I. (3) The vinyl monomer used in step II has a structure different from that of the oil-soluble monomer used in step I. (4) The organic solvent used in step II is a polyether having a molecular weight of 200 or more. (5) The concentration of the vinyl monomer used in step II is 30% by weight or less in the mixture in step II.

[0150] Preferred structures of the fifth monolith thus obtained include a continuous macropore structure ("5-1 monolith") in which bubble-like macropores overlap each other and the overlapping portions form openings with an average diameter of, for example, 10 to 120 μm in a dry state, and a co-continuous structure ("5-2 monolith") consisting of a three-dimensionally continuous skeleton with a thickness of, for example, 0.8 to 40 μm in a dry state and three-dimensionally continuous pores between the skeletons with a diameter of, for example, 8 to 80 μm in a dry state. The method for introducing cation exchange groups into the fifth monolith is the same as the method for introducing cation exchange groups into the first monolith.

[0151] [Conditions for producing carboxylic acid thioester] In the method for producing a carboxylic acid thioester according to the present embodiment, the reaction temperature is not particularly limited as long as the carboxylic acid and the thiol react in the presence of a strongly acidic cation exchange resin, but is, for example, in the range of 100 to 180° C., and preferably in the range of 120 to 160° C. If the reaction temperature is less than 100° C., the production efficiency may decrease, and if it exceeds 180° C., there is a concern that the strongly acidic cation exchange resin used as a catalyst may be decomposed or a side reaction may proceed.

[0152] The reaction time is not particularly limited as long as the reaction between the carboxylic acid and the thiol proceeds, but is, for example, in the range of 3 to 120 hours. If the reaction time is less than 3 hours, the reaction may not proceed sufficiently, and if the reaction time exceeds 120 hours, the production efficiency may not be improved.

[0153] In the method for producing a carboxylic acid thioester according to the present embodiment, the reaction between a carboxylic acid and a thiol can be carried out in a solvent. The type of solvent is not particularly limited as long as it does not inhibit the reaction between a carboxylic acid and a thiol, and examples thereof include hydrocarbon solvents such as octane and decane, aromatic solvents such as toluene and xylene, halogen solvents such as chlorobenzene, ether solvents such as 1,2-dimethoxymethane and diglyme, amide solvents such as N,N-dimethylformamide, sulfoxide solvents such as dimethyl sulfoxide, and sulfone solvents such as sulfolane. The solvent may be used alone or in a mixture of two or more types.

[0154] The reaction may be carried out under an inert gas atmosphere such as argon, nitrogen, etc. By carrying out the reaction under an inert gas atmosphere, discoloration of the reaction solution can be suppressed.

[0155] The carboxylic acid thioester obtained by the present production method may be purified by a purification step as necessary. The purification method is not particularly limited as long as it can improve the purity of the obtained carboxylic acid thioester, and examples of the purification method include silica gel flash column chromatography and recrystallization.

[0156] The reaction of carboxylic acid and thiol in the presence of a strong acid cation exchange resin may be carried out, for example, by introducing a raw material liquid (liquid to be treated) containing carboxylic acid and thiol into a filled container filled with a strong acid cation exchange resin as a solid acid catalyst through an inlet path of the filled container, passing the raw material liquid through the strong acid cation exchange resin, contacting it, and discharging the reaction liquid through a discharge path of the filled container. The filled container may be heated to a predetermined temperature by a heating device. Alternatively, the raw material liquid containing carboxylic acid, thiol, and strong acid cation exchange resin may be reacted in a reaction container, for example, under an inert gas atmosphere at a predetermined temperature for a predetermined time, while stirring as necessary. EXAMPLES

[0157] EXAMPLES The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0158] [Production of monolithic cation exchanger] (Manufacturing of Monolith Intermediate (Process I)) 9.28g of styrene as a monomer, 0.19g of divinylbenzene, 0.50g of sorbitan monooleate (hereinafter abbreviated as SMO) as a surfactant, and 0.25g of 2,2'-azobis(isobutyronitrile) as a polymerization initiator were mixed and dissolved uniformly. Next, this styrene / divinylbenzene / SMO / 2,2'-azobis(isobutyronitrile) mixture was added to 180g of pure water and stirred under reduced pressure using a planetary stirring device, a vacuum stirring and degassing mixer (manufactured by EME Co., Ltd.) to obtain a water-in-oil type emulsion. This emulsion was quickly transferred to a reaction vessel, sealed, and polymerized at 60°C for 24 hours under static conditions. After the polymerization was completed, the contents were removed, extracted with methanol, and then dried under reduced pressure to produce a monolith intermediate having a continuous macropore structure. The internal structure of the monolith intermediate (dried body) obtained in this manner was observed by SEM. An SEM image is shown in Figure 10. Although the wall separating two adjacent macropores is extremely thin and rod-like, it has a continuous macropore structure. The average diameter of the openings (mesopores) where the macropores overlap, as measured by mercury intrusion porosimetry, was 40 μm, and the total pore volume was 18.2 mL / g.

[0159] (Monolith Manufacturing (II Process)) Next, 216.6 g of styrene as a monomer, 4.4 g of divinylbenzene as a crosslinking agent, 220 g of 1-decanol as an organic solvent, and 0.8 g of 2,2'-azobis(2,4-dimethylvaleronitrile) as a polymerization initiator were mixed and dissolved uniformly (II step).

[0160] (Manufacturing of Monoliths (III Process)) Next, the monolith intermediate was placed in a reaction vessel, immersed in the styrene / divinylbenzene / 1-decanol / 2,2'-azobis(2,4-dimethylvaleronitrile) mixture, and degassed in a vacuum chamber. The reaction vessel was then sealed and allowed to polymerize for 24 hours at 50°C under static conditions. After polymerization was completed, the contents were removed, extracted with acetone using a Soxhlet extractor, and then dried under reduced pressure (III step).

[0161] The internal structure of the monolith (dried body) containing 1.2 mol% of a crosslinking component made of a styrene / divinylbenzene copolymer thus obtained was observed by SEM, and the results are shown in FIG. 11. As is clear from FIG. 11, the skeleton and pores of this monolith were three-dimensionally continuous, consisting of a continuous skeleton phase and a continuous pore phase, respectively, and the two phases were intertwined to form a co-continuous structure. The thickness of the continuous skeleton measured from the SEM image was 20 μm. The average diameter of the three-dimensionally continuous pores of this monolith, measured by mercury intrusion porosimetry, was 70 μm, and the total pore volume was 4.4 mL / g. The average diameter of the pores was determined from the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry.

[0162] (Production of monolithic cation exchanger) The monolith produced by the above method was placed in a column reactor, and a solution containing 500 g of chlorosulfonic acid and 4 L of dichloromethane was passed through it to react at 20°C for 3 hours. After the reaction was completed, methanol was added to the system to deactivate unreacted chlorosulfonic acid, and the product was extracted by washing with methanol. Finally, it was washed with pure water to obtain a monolith cation exchanger.

[0163] The cation exchange capacity of the obtained monolith cation exchanger in the dry state was 4.7 mg equivalent / g, and it was confirmed that sulfonic acid groups were quantitatively introduced. As is clear from FIG. 11, this monolith cation exchanger had a bicontinuous structure in which the framework and pores were three-dimensionally continuous and the two phases were entangled. The average width of the framework in the dry state measured from SEM images was 20 μm, and the average diameter of the three-dimensionally continuous pores of this monolith cation exchanger in the dry state measured from mercury intrusion porosimetry was 70 μm, and the total pore volume in the dry state was 4.4 mL / g.

[0164] Next, in order to confirm the distribution of sulfonic acid groups in the monolith cation exchanger, the distribution of sulfur was observed by an electron probe microanalyzer (EPMA). The distribution of sulfur on the surface of the monolith cation exchanger is shown in Figure 12, and the distribution of sulfur in the cross section of the skeleton is shown in Figure 13. It was confirmed that sulfur was distributed almost uniformly not only on the skeleton surface of the monolith cation exchanger but also inside the skeleton, and that sulfonic acid groups were introduced almost uniformly into the monolith cation exchanger.

[0165] The monolithic cation exchanger produced in this manner will hereinafter also be referred to as "monolith-SO3H" or "monolith-SO3H catalyst".

[0166] <Example 1-1> 75.1 mg (0.5 mmol) of 3-phenylpropionic acid (hereinafter also referred to as "PPA") as a substrate, 75.1 mg (100 mass%) of monolith-SO3H catalyst chopped into 1-2 mm squares with a knife, 238.1 μL (2 equivalents relative to the substrate) of 1-dodecanethiol (hereinafter also referred to as "DDT"), and 1 mL of toluene were placed in a dried test tube. After that, an argon balloon was attached and the atmosphere was replaced with argon, and the reaction temperature was set to 120 ° C. and stirred for 72 hours to react.

[0167] Ethyl acetate was then added to the reaction solution, and the mixture was filtered through a cotton plug to obtain a reaction filtrate from which the monolith-SO3H catalyst had been removed. Toluene and ethyl acetate were removed by distillation under reduced pressure, and the reaction residue was dissolved in deuterated chloroform, to which 1,1,2,2-tetrachloroethane (0.5 mmol) was added as an internal standard substance. 1 By measuring with HNMR (ECS-400, manufactured by JEOL Ltd.), the yields of the unreacted raw material substrate and the target product S-dodecyl 3-phenylpropanethioester (hereinafter also referred to as "DPT") were calculated to be 12% and 88% (corresponding to 147.2 mg), respectively. The results are shown in Table 1. When the reaction was carried out in the same manner at 60°C and 80°C, almost no target product was obtained.

[0168] <Example 1-2 to Example 1- 4, Reference example 1-5~Reference example 1-7 , Comparative Examples 1-1, 1-2> The reaction was carried out under the same conditions as in Example 1-1, except that the thiol equivalent, reaction temperature, reaction time, and catalyst in Example 1-1 were changed to those shown in Table 1, to obtain a mixed product. 1 The internal standard yield was calculated by HNMR (ECS-400 or ECA-500, manufactured by JEOL Ltd.). The results are shown in Table 1. "Amberlyst (trademark) 16WET" (cation exchange capacity: 4.8 mg equivalent / g), "Amberlyst (trademark) 15DRY" (cation exchange capacity: 4.7 mg equivalent / g), "Amberlyst (trademark) 45" (cation exchange capacity: 2.95 mg equivalent / g), and "Amberlite (trademark) XH2071H" (cation exchange capacity: 2.7 mg equivalent / g) listed in Table 1 are strongly acidic cation exchange resins manufactured by Organo Corporation.

[0169] [Table 1]

[0170] As can be seen from Table 1 ,strength Acidic Cation Exchange resin Under conditions using Amberlyst (trademark 45) (Comparative Example 1) and conditions not using a catalyst (Comparative Example 2), the target thioester could not be produced. non-particulate organic porous The coexistence of a strongly acidic cation exchanger is important.

[0171] In particular, it is seen from Example 1-1 that when monolith-SO3H is used as the strongly acidic cation exchanger, thioesterification proceeds and the target compound can be produced in high yield.

[0172] <Example 2-1> 75.1 mg (0.5 mmol) of 3-phenylpropionic acid (PPA) as a substrate, 75.1 mg (100 mass%) of monolith-SO3H catalyst chopped into 1-2 mm squares with a knife, 124.2 mg (2 equivalents to the substrate) of p-toluenethiol (hereinafter also referred to as "PTT"), and 1 mL of toluene were placed in a dried test tube. After that, an argon balloon was attached and the atmosphere was replaced with argon, and the reaction temperature was set to 120°C and the reaction was allowed to proceed with stirring for 72 hours.

[0173] Ethyl acetate was then added to the reaction solution, and the mixture was filtered through a cotton plug to obtain a reaction filtrate from which the monolith-SO3H catalyst had been removed. Toluene and ethyl acetate were removed by distillation under reduced pressure, and the reaction residue was dissolved in deuterated chloroform, to which 1,1,2,2-tetrachloroethane (0.5 mmol) was added as an internal standard substance. 1 By measuring HNMR, the yields of the unreacted raw material substrate and the target product S-(p-tolyl)-3-phenylpropanethioester (hereinafter also referred to as "TPT") were calculated to be 79% and 15% (corresponding to 19.2 mg), respectively. In addition, the mixed product was purified by column and isolated with an isolation yield of 14% (17.9 mg). The results are shown in Table 2.

[0174] <Example 2-2> The reaction was carried out under the same conditions as in Example 2-1, except that the thiol in Example 2-1 was changed to 1-heptanethiol (hereinafter also referred to as "HT") 157.5 μL (2 equivalents relative to the substrate), and a mixed product containing S-heptyl-3-phenylpropanethioester (hereinafter also referred to as "HPT") was obtained. The yields of the raw material substrate that remained unreacted and the target product HPT were calculated to be 0% and 96% (equivalent to 126.9 mg), respectively. In addition, the mixed product was purified by column and isolated with an isolation yield of 92% (121.7 mg). The results are shown in Table 2.

[0175] <Example 2-3> The reaction was carried out under the same conditions as in Example 2-1, except that the thiol in Example 2-1 was changed to 1-octanethiol (hereinafter also referred to as "OT") 174.2 μL (2 equivalents relative to the substrate), and a mixed product containing S-octyl-3-phenylpropanethioester (hereinafter also referred to as "OPT") was obtained. The yields of the raw material substrate that remained unreacted and the target product OPT were calculated to be 0% and 98% (corresponding to 136.4 mg), respectively. In addition, the mixed product was purified by column and isolated with an isolation yield of 90% (125.3 mg). The results are shown in Table 2.

[0176] <Example 2-4> The reaction was carried out under the same conditions as in Example 2-1, except that the raw substrate in Example 2-1 was changed to 61.1 mg (0.5 mmol) of benzoic acid (hereinafter also referred to as "BA"), and a mixed product containing S-(p-tolyl)-benzothioester (hereinafter also referred to as "TBT") was obtained. The yields of the raw substrate remaining unreacted and the target product TBT were calculated to be 50% and 44% (corresponding to 50.2 mg), respectively. In addition, the mixed product was purified by column and isolated with an isolation yield of 44% (49.8 mg). The results are shown in Table 2.

[0177] <Example 2-5> The reaction was carried out under the same conditions as in Example 2-1, except that the raw substrate in Example 2-2 was changed to 61.1 mg (0.5 mmol) of benzoic acid (BA), to obtain a mixed product containing S-heptyl benzothioester (hereinafter also referred to as "HBT"). The yields of the raw substrate remaining unreacted and the target product HBT were calculated to be 0% and 97% (corresponding to 114.6 mg), respectively. In addition, the mixed product was purified by column purification and isolated with an isolation yield of 94% (111.1 mg). The results are shown in Table 2.

[0178] <Example 2-6> The reaction was carried out under the same conditions as in Example 2-1, except that the raw substrate in Example 2-3 was changed to 61.1 mg (0.5 mmol) of benzoic acid (BA), to obtain a mixed product containing S-octylbenzothioester (hereinafter also referred to as "OBT"). The yields of the raw substrate remaining unreacted and the target product OBT were calculated to be 0% and 100% (equivalent to 124.2 mg), respectively. In addition, the mixed product was purified by column and isolated with an isolation yield of 100% (125.0 mg). The results are shown in Table 2.

[0179] <Example 2-7> 53.1 mg (0.5 mmol) of benzaldehyde (hereinafter also referred to as "BDA") as a substrate, 53.1 mg (100 mass%) of monolith-SO3H catalyst, 100.2 μL (2 equivalents relative to the substrate) of 1,3-propanedithiol (hereinafter also referred to as "PDT"), and 1 mL of toluene were placed in a dried test tube. After that, an argon balloon was attached and the atmosphere was replaced with argon, and the reaction temperature was set to 120 ° C. and the reaction was allowed to proceed with stirring for 72 hours.

[0180] Ethyl acetate was then added to the reaction solution, and the mixture was filtered through a cotton plug to obtain a reaction filtrate from which the monolith-SO3H catalyst had been removed. Toluene and ethyl acetate were removed by distillation under reduced pressure, and the reaction residue was dissolved in deuterated chloroform, to which 1,1,2,2-tetrachloroethane (0.5 mmol) was added as an internal standard substance. 1 By measuring HNMR, the yields of the unreacted raw material substrate and the target product 2-phenyl-1,3-dithiane (hereinafter also referred to as "PDT") were calculated to be 0% and 91% (equivalent to 89.3 mg), respectively. In addition, the mixed product was purified by column and isolated with an isolation yield of 89% (87.2 mg). The results are shown in Table 2.

[0181] [Table 2]

[0182] Thus, the method of the embodiment is a method which is easy to operate, can reduce the amount of waste, and is sustainable. [Explanation of symbols]

[0183] 1 skeletal phase, 2 pore phase, 10 bicontinuous structure, 11 rectangular image area, 12 skeletal part, 13 macropore, 21 skeletal surface, 22a, 22b, 22c, 22d, 22e protrusions.

Claims

1. A method for producing a carboxylic acid thioester, comprising reacting a carboxylic acid with a thiol in the presence of a solid acid catalyst to produce a carboxylic acid thioester, the method comprising the steps of: The method for producing a carboxylic acid thioester, wherein the solid acid catalyst is a non-particulate organic porous strongly acidic cation exchanger.

2. A method for producing the carboxylic acid thioester according to claim 1, comprising the steps of: The method for producing a carboxylic acid thioester, wherein the non-particulate organic porous strongly acidic cation exchanger has a cation exchange capacity of more than 1 mg equivalent / g.

3. A method for producing a carboxylic acid thioester according to claim 1 or 2, comprising the steps of: The non-particulate organic porous strongly acidic cation exchanger comprises a continuous skeleton phase and a continuous pore phase, the thickness of the continuous skeleton being in the range of 1 to 100 μm, the average diameter of the continuous pores being in the range of 1 to 1000 μm, the total pore volume being in the range of 0.5 to 50 mL / g, and the cation exchange capacity per weight in a dry state being in the range of 1 to 5 mg equivalent / g, and the cation exchange groups being distributed throughout the non-particulate organic porous strongly acidic cation exchanger.

Citation Information

Patent Citations

  • Method of direct synthesis of thioester

    JP2003155271A

  • Separator for proton conductive polymer secondary battery and proton conductive polymer secondary battery

    JP2005093123A

  • Solid acid catalyst

    JP2010264346A

  • Solid acid catalyst

    JP2011036806A

  • Method for producing ester compound

    JP2017171623A